Inside the sixties : g.p. 1.2.3. : le salon international de galeries-pilotes à Lausanne 1963 1966 1970. - Armleder, John; Aupetitallot, Yves; Berger, René; Bovier, Lionel; Cherix, Christophe; Keller, Pierre; Lombardi, Sarah; Nicod, Caroline; Williams, Parker; Wyder, Bernard; Musée cantonal des beaux-arts Lausanne (Lausanne : Musée Cantonal des Beaux-Arts Lausanne, 2002)
Armleder, John ; Keller, Pierre ; Mosset, Olivier ; Broodthaers, Marcel ; Saito, Yoshishige ; Yoshihara, Michio ; Michenet, Roland ; George, Thomas ; Heyboer, Anton ; Kantor, Tadeusz ; Lichtenstein, Roy ; Warhol, Andy ; Rosenquist, James ; Wesselmann, Tom ; Rauschenberg, Robert ; Capogrossi, Giuseppe ; Soulages, Pierre ; Baj, Enrico ; Crippa, Roberto ; Pezzo, Lucio Del ; Hultberg, John ; Lataster, Ger ; Lucebert ; Schumacher, Emil ; Szenes, Arpad ; Alviani, Getulio ; Sutej, Miroslav ; Arman ; Baj, Enrico ; Baertling, Olle ; Takis ; Fontana, Luciano ; Tobey, Mark
geselect. Bibliog. p. 124-127
Engels
Frans
Inside the sixties : g.p. 1.2.3., Musée Cantonal des Beaux-Arts Lausanne, 24 mai - 15 septembre 2002
boek